Lepidoptera del Pantepui. Parte VIII Nuevos Nymphalidae (Charaxinae y Satyrinae) y Riodinidae (Riodininae). / Lepidoptera from the Pantepui. Part VIII New Nymphalidae (Charaxinae and Satyrinae) and Riodinidae (Riodininae) - Costa, Mauro; Viloria, Ángel L.; Attal, Stéphane; Neild, Andrew F. E.; Fratello, Steven; Benmesbah, Mohamed (Anartia, 2020)
RESUMEN Se describen dos nuevas subespecies y dos especies de Lepidoptera (Papilionoidea) de la porción venezolana del Pantepui: Memphis paulus clarae Attal & Costa, ssp. nov. (Charaxinae, Anaeini), Stalachtis halloweeni miranda Costa & Fratello, ssp. nov. (Riodininae, Stalachtini), Forsterinaria chaniorum Viloria & Costa, sp. nov. y Euptychia sarah Benmesbah & Viloria, sp. nov. (Satyrinae, Satyrini). La primera subespecie se suma a un grupo de taxones aparentemente endémicos del Auyán Tepui; este tipo de evidencia sugiere la posibilidad de que la meseta del Auyán represente un distrito biogeográfico dentro de la Provincia del Pantepui. ABSTRACT Two new subspecies and two species of Lepidoptera (Papilionoidea) are described from the Venezuelan portion of the Pantepui: Memphis paulus clarae Attal & Costa, ssp. nov. (Charaxinae, Anaeini), Stalachtis halloweeni miranda Costa & Fratello, ssp. nov. (Riodininae, Stalachtini), Forsterinaria chaniorum Viloria & Costa, sp. nov. and Euptychia sarah Benmesbah & Viloria, sp. nov. (Satyrinae, Satyrini). The first subspecies joins a group of taxa apparently endemic to the Auyán Tepui; this kind of evidence suggests the possibility that the Auyán table mountain represents a biogeographic district within the Pantepui Province.